Perancangan User Experience Aplikasi Booking Servis Mobil Menggunakan Metode Human-Centered Design - Debie Shabastian Rosie; Hanifah Muslimah Az-Zahra; Alfi Nur Rusydi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Langgeng Motor car repair shop customers have high mobility but do not have sufficient information about the workshop capacity which makes customers uncertain about getting car service and causes the workshop to get poor reviews. This study aims to design a Langgeng App's User Experience as a solution that has good Usability and User Experience values. The Human-Centered Design approach is used with due regard to the User Experience element. Starting from analyzing the user context, analyzing user needs, and creating a solution design. Design evaluation using Usability Testing produces an effectiveness value of 96.9% for the customer user group and 97.5% for the workshop employee user group and is in a good category or above 78% and an efficiency value of 90.7% for customers and 90.83% for workshop employees. Customer satisfaction is positive or above 0.8 which is known from the UEQ Hedonic Quality aspect. User Experience Questionnaires are given after testing and get a